Batas Usia Nikah dan Kedewasaan dalam Pernikahan Menurut Al Qur'an: Studi Terhadap QS. An-Nisa Ayat 6 - Annisa Rahmadani; Muhammad Hidayat (Ta’wiluna: Jurnal Ilmu Al-Qur'an, Tafsir dan Pemikiran Islam, 2025)
This research examines the phenomenon of marriage at a young age in Indonesia by emphasizing the minimum age for marriage and the notion of maturity according to the view of the Qur'an through the analysis of QS. The background of the research comes from the social, legal, and cultural developments that underlie the practice of early marriage, as well as policy changes through Law Number 16 of 2019 which equalizes the age of marriage for men and women to 19 years. The method used in this research is qualitative with a library research approach and thematic tafsir analysis (al-maudu'i). The research findings show that maturity (rusyd) in the Qur'an is not only seen from a biological point of view (baligh), but also includes psychological, intellectual, social, and moral dimensions, as well as financial obligations and conditions. Therefore, this research provides a new perspective on marriage that is not only legal formal, but also prioritizes mental, emotional, and spiritual readiness. Hopefully, this can be an alternative solution to prevent early marriage while strengthening the development of a harmonious, loving and happy family in this modern era.